1999
DOI: 10.1021/ac981302a
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Concept for Stacking Neutral Analytes in Micellar Capillary Electrophoresis

Abstract: Unlike recent studies that have depended on manipulation of separation buffer parameters to facilitate stacking of neutral analytes in micellar capillary electrophoresis (MCE) mode, we have developed a method of stacking based simply on manipulation of the sample matrix. Many solutions for sample stacking in MCE are based on strict control of pH, micelle type, electroosmotic flow (EOF) rate, and separation-mode polarity. However, a universal solution to sample stacking in MCE should allow for free manipulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
173
1
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(184 citation statements)
references
References 25 publications
7
173
1
2
Order By: Relevance
“…Researchers found that having high electric field strength in the sample zone, which can cause adverse effects, is not required. They also found that the sample matrix can be prepared in a buffer solution with conductivity that is similar or higher than BGS and without adding micelle (15). Under these conditions, no enhanced field strength will be generated and electrophoretic migration and EOF will not change the velocity from the sample zone to the BGS zone.…”
Section: Sensitivity Enhancementmentioning
confidence: 99%
“…Researchers found that having high electric field strength in the sample zone, which can cause adverse effects, is not required. They also found that the sample matrix can be prepared in a buffer solution with conductivity that is similar or higher than BGS and without adding micelle (15). Under these conditions, no enhanced field strength will be generated and electrophoretic migration and EOF will not change the velocity from the sample zone to the BGS zone.…”
Section: Sensitivity Enhancementmentioning
confidence: 99%
“…Under these conditions where the sample contains salts with a concentration higher than the BGE, a stacked SDS zone may be formed due to the difference in the electric fields between the BGE zone and the sample zone. 9,10 The micelles that are formed at the interface between the BGE zone and the sample zone result in a sharp peak. As a result, the methylene blue zone is partly stacked by interactions with the SDS micelles in the stacked SDS zone.…”
Section: Effect Of the Sds Concentration In The Bgementioning
confidence: 99%
“…9,10 The mechanism for this process is currently unclear. 10,11 However, an analogous method seems to be potentially useful for not only small molecules, but proteins, because proteins form anionic protein-SDS complexes via binding interactions (hydrophobic interaction) with SDS, resulting in a decrease in the electrophoretic velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Sweeping is representative of this group [5]. Among them, sample stacking and sweeping are most frequently used in MEKC [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Sample stacking techniques in RM-MEKC mode using low-pH phosphate buffers have been shown to be very good [10,12,13]. Landers and co-workers [15][16][17][18] used a different strategy to preconcentrate neutral analytes in MEKC. In contrast to conventional stacking approaches, the sample matrix in these cases has a higher salt content (as well as conductivity) than the BGE, which permits the efficient stacking of micelles in the BGE zone prior to interaction with the neutral analytes in the sample zone.…”
Section: Introductionmentioning
confidence: 99%